Optimal stopping in “The Showcase Showdown”. - Coe, Paul R.; Butterworth, William (American Statistician, 1995)
“The Showcase Showdown,” one of the games routinely played on the TV game show The Price is Right, is an excellent example of the use of elementary probability to solve a practical problem. The game involves many of the subjects typically covered in applied probability, namely, axioms of probability, conditional probability, combinatorics, and computer simulation. “The Showcase Showdown” involves spinning a large wheel with the nickel values 5,10,15,...,100 on it. The object of the game is to achieve the highest score, from one or two spins, of all of the players in the game without going over a dollar (100). The writers employ conditional probability and a Pascal computer program to derive the optimal stopping time for all three players in the usual game.